38.5=2x-1.5+2x-1.5+x+x+x+7.2

Simple and best practice solution for 38.5=2x-1.5+2x-1.5+x+x+x+7.2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 38.5=2x-1.5+2x-1.5+x+x+x+7.2 equation:


Simplifying
38.5 = 2x + -1.5 + 2x + -1.5 + x + x + x + 7.2

Reorder the terms:
38.5 = -1.5 + -1.5 + 7.2 + 2x + 2x + x + x + x

Combine like terms: -1.5 + -1.5 = -3
38.5 = -3 + 7.2 + 2x + 2x + x + x + x

Combine like terms: -3 + 7.2 = 4.2
38.5 = 4.2 + 2x + 2x + x + x + x

Combine like terms: 2x + 2x = 4x
38.5 = 4.2 + 4x + x + x + x

Combine like terms: 4x + x = 5x
38.5 = 4.2 + 5x + x + x

Combine like terms: 5x + x = 6x
38.5 = 4.2 + 6x + x

Combine like terms: 6x + x = 7x
38.5 = 4.2 + 7x

Solving
38.5 = 4.2 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
38.5 + -7x = 4.2 + 7x + -7x

Combine like terms: 7x + -7x = 0
38.5 + -7x = 4.2 + 0
38.5 + -7x = 4.2

Add '-38.5' to each side of the equation.
38.5 + -38.5 + -7x = 4.2 + -38.5

Combine like terms: 38.5 + -38.5 = 0.0
0.0 + -7x = 4.2 + -38.5
-7x = 4.2 + -38.5

Combine like terms: 4.2 + -38.5 = -34.3
-7x = -34.3

Divide each side by '-7'.
x = 4.9

Simplifying
x = 4.9

See similar equations:

| 33.9ab-82.4ac+29.3ad-84.8ac+73.2ab= | | y-17=-33 | | 2x-20=36.37 | | 9.9x+38.57=-10.1+38.41b | | 108=x+x+3.5x+3.5x | | Y^2+2y-24=0 | | 66.8=2x+4.7+2x+4.7+2x+4.7+2x+4.7 | | (c-3)(c-3)=o | | x+4=9x-72 | | 9(3+x)= | | 27y^2-52y+25= | | 66.8=2x+4.7 | | 5p-(4p-4)=17 | | 19.8=x+2.9+4.5+x | | 9.9x+38.57=-10.1+38.41 | | 15(x+1)=5(4x) | | y=zr | | p=0.4+-350.002x | | 2w^9-20w^8-48w^7= | | p=1.4+-350x-1+-0.002x | | 1(t-4)+7t=4(2t+3)-8 | | 15x+15=20x | | p(x)=-0.002x^2+1.4x-350 | | 7.4x-2.9=11.9 | | 1.95x-4.38z+2.83a-5.21z-9.27x= | | v+(v-16)+3(30-v)=641 | | 3a+4=24 | | h=32+14t-1+-16t | | -(6x+3)-(-5x-8)=3 | | (9-x)(3x+5)=0 | | -x-18+2x+4=6x+24 | | a-6b+2c+a-6b+n-2c= |

Equations solver categories